Assessing the "Reach" of a Fire-Based Mobile Integrated Health Buprenorphine Induction Program Through an Implementation Science Lens. - Engel II, Thomas W.; Hernandez-Meier, Jennifer; Comstock, Grant; Fumo, Nicole; Mueller, Daria; Kovacevich, Hannah; Pojar, Dan; Schaak, Jason; Weston, Benjamin W. (Prehospital Emergency Care, 2025)
Objectives: Medication for opioid use disorder (MOUD) reduces morbidity and mortality for patients with opioid use disorder (OUD). Recent administrative and legislative changes have made MOUD possible in the prehospital setting. We use an implementation science framework to outline the Reach of a fire department EMS-based Mobile Integrated Health (MIH) prehospital MOUD program. Methods: The West Allis Fire Department (WAFD) within the Milwaukee County EMS system operates an MIH program that allows for internal and external referrals for patients with OUD. Internal referrals originated from 9-1-1 dispatch via emergency medical dispatch code selection, self-dispatch, or a weekly summary of electronic patient care reports involving opioid-related encounters. External referrals came from emergency departments (ED) or community partners. Among all referral patients with OUD, the primary measures included Overall Reach (those who agreed to MIH services), Clinical Opiate Withdrawal Scale (COWS) Reach (those with a COWS score performed), Buprenorphine Reach (those who based on COWS were offered buprenorphine induction) and Induction Reach (those who accepted buprenorphine induction). Results: Between 5/24/2023 and 5/25/2024, the WAFD MIH program received 265 total potential OUD patient referrals, 135 internally and 130 externally. Internal referrals consisted of 48 MIH responses received from 9-1-1 dispatch, 5 self-dispatches, and 82 patients captured on a weekly report. In the external referral process, 8 originated from community partners and 122 from EDs. Among the combined 265 patient referrals, 128 (48.3%) patient contacts were made. The Overall Reach was 99/128 patients (77.3%), COWS Reach was 99/99 (100%), Buprenorphine Reach was 8/99 (8.1%) patients, and Induction Reach was 4/8 (50%). Conlusions: A fire department EMS-based MIH buprenorphine MOUD program is able to reach patients experiencing OUD. External partners make up a sizable proportion of patient referrals to increase a program's reach. Challenges included obtaining real time assessment from designated MIH clinicians utilizing dispatch protocols, a high proportion of ineligible patients based on buprenorphine guidelines, and a relatively high proportion of patients declining induction. Results may assist other fire departments in assessing potential estimates of patient encounters and avenues for patient contact for similar programing.